1981
DOI: 10.1111/j.1651-2227.1981.tb06252.x
|View full text |Cite
|
Sign up to set email alerts
|

BLOOD PESTICIDE CONCENTRATION IN MOTHERS AND THEIR NEWBORN INFANTS: Relation to Prematurity

Abstract: An association between high DDT cord blood levels and prematurity was investigated. Pregnant women with good health and nutritional condition, negative history of past occupational exposure to DDT and absence of recent exposure to DDT were investigated as well as their appropriate for gestational age neonates. A total of 54 maternal-infant pairs were studied and divided in two groups: A-term deliveries (30 pairs), B-preterm deliveries (24 pairs). There was no difference in DDT blood levels between pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 12 publications
(3 reference statements)
0
10
0
Order By: Relevance
“…Moreover, organochlorines readily cross the placenta; neonatal blood levels attain about one-third the maternal values. In a study from Brazil, based on a population with a high (44%) incidence of preterm births, Procianoy and Schvartsman [1981] reported significantly higher levels in cord blood of preterm compared to normal term deliveries, but maternal levels did not distinguish preterm from normal births. Saxena et al [1981] noted substantially higher levels of DDT in placental tissue and in maternal blood from premature abortions than from term infants.…”
Section: Developmental Neurotoxicity Of Other Organochlorine Compoundsmentioning
confidence: 93%
“…Moreover, organochlorines readily cross the placenta; neonatal blood levels attain about one-third the maternal values. In a study from Brazil, based on a population with a high (44%) incidence of preterm births, Procianoy and Schvartsman [1981] reported significantly higher levels in cord blood of preterm compared to normal term deliveries, but maternal levels did not distinguish preterm from normal births. Saxena et al [1981] noted substantially higher levels of DDT in placental tissue and in maternal blood from premature abortions than from term infants.…”
Section: Developmental Neurotoxicity Of Other Organochlorine Compoundsmentioning
confidence: 93%
“…In neither study were case-control differences evident. Data from several small studies (88,97,98) showed cord tissue or cord blood DDT (mostly p,p -DDE) levels were higher in premature infants than in term infants. The importance of these findings, however, is unclear owing to the possibility that the results are confounded by lipid levels or risk factors for prematurity, and because early fetal loss was not assessed in these studies.…”
Section: Data On Human Health Effectsmentioning
confidence: 99%
“…DDT levels were not found to be higher in blood of women who had spontaneous abortions than in those who had normal pregnancies (118). Procianoy & Schvartsman (134) found that mothers of preterm (M=33 wk) and term infants had comparable DDT levels. However, Saxena et al (142) found that women having spontaneous abortions and mothers of premature infants had 10 times the DDT levels of mothers with term infants.…”
Section: Organochlorine Pesticidesmentioning
confidence: 99%
“…They suggested that the latter hypothesis is supported by the significant negative correlation of birth weight and DDT levels. However, in a larger study (36) of women and their newborns (n=350), where only 3% of the infants were preterm [compared to 44% in Procianoy & Schvartsman's study (134)], birth weight did not correlate significantly with DDT levels.…”
Section: Organochlorine Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation